Inflammaging as a link between autoimmunity and cardiovascular disease: the case of rheumatoid arthritis. Issue 1 (19th January 2021) - Santos-Moreno, Pedro; Burgos-Angulo, Gabriel; Martinez-Ceballos, Maria Alejandra; Pizano, Alejandro; Echeverri, Dario; Bautista-Niño, Paula K; Roks, Anton J M; Rojas-Villarraga, Adriana
Abstract : Currently, traditional and non-traditional risk factors for cardiovascular disease have been established. The first group includes age, which constitutes one of the most important factors in the development of chronic diseases. The second group includes inflammation, the pathophysiology of which contributes to an accelerated process of vascular remodelling and atherogenesis in autoimmune diseases. Indeed, the term inflammaging has been used to refer to the inflammatory origin of ageing, explicitly due to the chronic inflammatory process associated with age (in healthy individuals). Taking this into account, it can be inferred that people with autoimmune diseases are likely to have an early acceleration of vascular ageing (vascular stiffness) as evidenced in the alteration of non-invasive cardiovascular tests such as pulse wave velocity. Thus, an association is created between autoimmunity and high morbidity and mortality rates caused by cardiovascular disease in this population group. The beneficial impact of the treatments for rheumatoid arthritis at the cardiovascular level has been reported, opening new opportunities for pharmacotherapy.